A primeira sonata para violino e piano de José Siqueira (1949): um estudo analítico e performático - Couto, Juliana Santos Rezende de Araújo (2023)
The main goal of this work is to carry out an analytical and performative study, focusing on northeastern musical genres (baião and maracatu), mainly in terms of rhythmic and modal characteristics present in the First Sonata for Violin and Piano (1949), by José Siqueira. In the first chapter we carry out a brief contextualization about the composer José Siqueira and his relationship with northeastern music, in addition to explaining the northeastern musical genres present in the work. Still, we address some theoretical and practical aspects of the trimodal system developed by the composer and briefly expose the classical sonata form to guide the analysis of the work. In the second chapter, we focused on the analytical study of the three movements of the work, analyzing it formally, harmonically/modally, thematically, and rhythmically, using William Caplin's (Classical Form, 1998) and James Hepokoski's works as theoretical references. and Warren Darcy (Elements of Sonata Theory, 2006). Finally, in the last chapter, we approach the performance construction process of the work, in which we selected some excerpts from the three movements, where we brought suggestions of an interpretative nature, in which they were based on the understanding of the style of the northeastern musical elements present in the work. We reviewed the bows, fingerings, dynamics and articulations indicated in the score, aspects for which we recommend some changes, as a contribution to a better understanding of the composer's idea.